Surface roughness measurement through a speckle method - Russo, Nélida Araceli (1990)
An optical approach for real-time measurement of statistical parameters associated with rough surfaces is proposed. Two crossed polarized, partially correlated, speckle patterns originated from a surface under different illumination conditions arc recorded on a linear photodiode array. The r.m.s. surface roughness is related to the correlation degree between both speckle patterns, which in turn is derived by processing the detected intensity distribution. Some experimental results are shown in order to illustrate this technique.